Estudo da fotoinativação de Saccharomyces cerevisiae utilizando lipossomas e proteínas de Moringa oleifera como sistemas de entrega de fotosensibilizadores sintéticos e naturais - Garcês, Bruno Pereira (2014)
Photodynamic therapy (PDT) is a treatment for cancer and certain non-malignant diseases, which are generally characterized by overgrowth of unwanted or abnormal cells. This technique uses a photosensitizer, light and oxygen to inactivate cells. In this work the photodynamic effects of synthetic photosensitizers chloroaluminum phthalocyanine, zinc phthalocyanine, methylene blue and toluidina blue and crude and parcially fracionated extracts of Bidens sulphurea, known as \"Picão laranja\" over Saccharomyces cerevisiae cultures was studied, because this yeast has a great energetic and structural similarity to cancer cells. To enhance the activity of the photosensitizers were used additives as Moringa oleifera agglutinating protein and albumin and these drugs were also encapsulates in phosphatidylcoline liposomes with cholesterol, poliethyleneglicol and albumin. The times of incubation and irradiation, the distance between the irradiation systems and the cells and the minimum inhibitory concentration of the photosensitizers were also standardized. The results showed that the Moringa oleifera agglutinating proteins were more efficient than liposome as Drug Delivery Systems. The extracts of Bidens sulphurea showed to be efficient to the photodynamic inactivation, being a potential source for the search for new photosensitizers.